THE ROLE OF NEONOMINATION IN EXPANDING THE VOCABULARY OF THE RUSSIAN LANGUAGE - Tamara Turumova; Gulara Tangriberganova (Web of Journals Publishing, 2024)
This article examines the role of neonominations in replenishing the vocabulary of the Russian language, and discusses the intralinguistic and extralinguistic causes of the emergence of new speech elements.
Keywords: language fashion, lexicon, morpheme, Anglicisms, word production, word-formation model, internationalization.